BS EN IEC 61753-085-2. Fibre optic interconnecting devices and passive components performance standard. Part 085-2. Non-connectorized single-mode pigtailed CWDM devices for category C. Indoor controlled environment (10th December 2019) - British Standards Institution,
No abstract available